Hubungan Antara Lamanya Menderita Diabetes Mellitus Tipe 2 Dengan Fungsi Kognitif Di GRHA Diabetika Surakarta - Fitriani, Reni; , Dwi Rosella K.S. S.Fis., M.Fis., Dipl.CIDESCO (2017)
Background : diabetes mellitus (DM) is a group of metabolic diseases with characterised of hyperglycemia that occurs due to abnormal insulin secretion, insulin action, or both. Type 2 diabetes mellitus is a chronic disease that is highly prevalent in Indonesia. PERKENI report in 2015 showed that Indonesia was the world's fifth position. Objective : The study aimed to determine the relationship of the duration of type 2 diabetes mellitus with cognitive and the confounding variables of family support. Method : the research design methode is observational study with cross sectional approach.The population of this study were patients with type 2 diabetes mellitus in GRHA Diabetic Surakarta as many as 218 people. The sample was determined by purposive sampling as many as 110 people. The Mini Mental Stage (MMSE) was used instrument to collect data. Data were tested by Korelation Product Moment Test and Spearman Rank Test. Result : The result of correlation study by Correlation Product Moment Test is a relationship between duration of type 2 diabetes mellitus with cognitive function shows p-value=0,0001 which means that there is relationship between two variables. While the result of correlation study by Spearman Rank Test is a relationship between family support with cognitive function shows p-value= 0.0001 which means that there is a relationship between two variables.